Reflecting on 'Beyond Positivism' at thirty-five - Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2017)
In 1982 my book Beyond Positivism: Economic Methodology in the Twentieth Century was published. At the 2017 History of Economics society meeting, a session was held to mark the 35th anniversary of that event. Papers by Wade Hands, Kevin Hoover, Tony Lawson, and the trio Peter Boettke, Solomon Stein and Virgil Storr were prepared. In this paper, I respond by reflecting on how I came to write Beyond Positivism and on the state of the field of economic methodology at the time, and then commenting briefly on each of the papers noted above.
Keywords: B2; B25; B4; B41; B53; 330; positivism; methodology of economics; philosophy of science; methodological pluralism; instrumentalism; theory choice; Karl Popper; Friedrich Hayek; complex phenomena; basic economic reasoning